Ageing-induced shrinkage of intervessel pit membranes in xylem of Clematis vitalba modifies its mechanical properties as revealed by atomic force microscopy - Carmesin, Cora F.; Port, Fabian; Böhringer, Samuel; Gottschalk, Kay-Eberhard; Rasche, Volker; Jansen, Steven (Frontiers in Plant Science, 2023)
Bordered pit membranes of angiosperm xylem are anisotropic, mesoporous media between neighbouring conduits, with a key role in long distance water transport. Yet, their mechanical properties are poorly understood. Here, we aim to quantify the stiffness of intervessel pit membranes over various growing seasons. By applying an AFM-based indentation technique “Quantitative Imaging” we investigated the Apparent elastic modulus of intervessel pit membranes of Clematis vitalba in dependence of size, age, and hydration state. The indentation-deformation behaviour was analysed with a non-linear membrane model, and paired with magnetic resonance imaging to visualise sap-filled and embolised vessels, while geometrical data of bordered pits were obtained using electron microscopy. An aspiration pressure was calculated. The Apparent elastic modulus of fresh pit membranes was with 57 MPa considerably lower than previously suggested. The estimated pressure for pit membrane aspiration was 2.20±\ 1.28 MPa. Pit membranes from older growth rings were shrunken and had a higher elastic modulus, suggesting an irreversible, mechanical ageing process. This study provides an experimental-stiffness analysis of hydrated intervessel pit membranes in their native state. The estimated aspiration pressure suggests that membranes are not deflected under normal field conditions. Although absolute values should be interpreted carefully, our data from hydraulically non-functional conduits suggest that pit membrane shrinkage implies increasing stiffness, and highlight the dynamic changes of pit membrane mechanics and their complex, functional behaviour for fluid transport.